Pelatihan Implementasi Kurikulum Merdeka pada Guru di Lembaga Paud Se-Kecamatan Madiun - Anwar, Rosyida Nurul (Communautaire: Journal of Community Service, 2022)
The curriculum is essential in fulfilling an education's direction and goals. The curriculum is a school system to obtain the expected results in situations inside and outside the school. The Independent Curriculum is an additional option for learning recovery during 2022-2024. In efforts to run the Independent Curriculum to the fullest, the teacher occupies an essential and central role in making the curriculum run well. This community service activity aims to provide an understanding of the readiness of teachers to implement the Independent Curriculum in their education units. The method is through lectures and discussions between participants in the Education unit. A questionnaire using a Likert scale is a method of evaluating this activity. 42 members of the IGTKI Madiun District attended this community service activity. The result of this service is that there is an understanding of participants in implementing the independent curriculum, and participants feel the benefits of this training activity.